Analisis Tingkat Utang, Likuiditas, dan Solvabilitas terhadap Profitabilitas Perusahaan Teknologi di Indonesia - Hotben Hotben; Rusliyawati Rusliyawati; Nina Febriana Dosinta (Penerbit Goodwood, 2025)
Purpose: This study provides recent empirical evidence on the effect of capital structure debt level, liquidity, and solvency on the profitability of Indonesian technology companies during 2019-2023. Methodology/approach: A quantitative case study was conducted using panel data from financial reports of IT and online service companies listed on the IDX (2019–2023). Financial ratios (DAR, CR, DER, ROA) were analyzed using EViews 12 with purposive sampling and panel data regression. Results: The study found no significant simultaneous effect of DAR, CR, and DER on ROE. Partially, liquidity had a significant positive effect, solvency has a significant impact, though it indicated a potential positive relationship if managed properly. The finding indicate that although debt level, liquidity, and solvency do not have a simultaneous significant impact on profitability, liquidity and solvency individually play a key role in influencing financial performance. This highlights the importance of maintaining strong liquidity and managing solvency effectively in the technology sector. Conclusion: Partially, only the Current Ratio (CR) has a significant positive effect on ROA, while DAR and DER are not significant. However, simultaneously the three variables have a significant effect with a contribution of 16.53%, emphasizing the importance of liquidity management in improving the profitability of technology companies. Limitations: The study is limited by sample size, lack of moderating variables, exclusion of other influencing factors, and a single method quantitative approach. Contribution: The study serves as a reference for company management in financial planning, for investors in conducting analysis, and for academics as a basis for future research exploring new variables, periods, sectors, or methods.